Virtual Learning Communities: A Contribution to the Pre-Service Teachers’ Learning - Herrera Mateus, Catalina; Herrera Varela, Brenda Julieth; García Arjona, John Jairo (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This paper presents the pre-service teachers’ learning of didactics and language teaching methodologies during their participation in a virtual learning community. Three main concepts were defined: Virtual Learning Communities (VLCs), reflective practice, and learning from a sociocultural perspective. 25 pre-service teachers from a bachelor’s degree in language teaching participated in the VLC. A focus group and the pre-service teacher’s reflection in the VLC were used to collect information. The results show pre- service learned to reflect on and use effective teaching materials; to select, adapt and combine language teaching methodologies, and to criticize themselves, their lessons plan, and their performance in order to improve their teaching practice.